Novel trispecific killer engager targeting B7-H3 enhances natural killer cell antitumor activity against head and neck cancer - Jeffrey S Miller; Martin Felices; Peter Hinderlie; James Lim; Naomi Fujioka; Shee Kwan Phung; Yvette Soignier; Joshua T Walker; Melissa A Geller; Madison Shackelford; Carly Selleck; Philippa R Kennedy; et al. (Journal for ImmunoTherapy of Cancer)
Background Patients with head and neck squamous cell carcinoma (HNSCC), particularly the human papillomavirus negative (HPV−) subset, have a dismal prognosis. Furthermore, patients with Fanconi anemia (FA) have a genetic predisposition with a 500-fold to 700-fold higher incidence of HNSCC. Thus, novel and more efficacious therapies are needed. As current immunotherapies often fail due to suppressive elements in the tumor microenvironment (TME), we developed a trispecific killer engager (TriKE) to direct multiple signals to natural killer (NK) cells to overcome the hypoxic TME. This TriKE is comprised of a camelid nanobody that binds to CD16 on NK cells, an interleukin (IL)-15 moiety, and another novel camelid nanobody that binds to the B7-H3 antigen, which is highly and specifically expressed on the tumor cell surface.Methods The B7H3 TriKE was generated using a mammalian expression system. Its functionality was evaluated using flow cytometry-based NK cell degranulation, cytokine production, proliferation and live cell imaging cytotoxicity assays. Models of acute and prolonged hypoxia (1% oxygen) were carried out to assess tumor killing. Tumor progression, NK cell persistence, and survival differences between IL-15-treated and TriKE-treated mice were studied using NOD-scidIL2Rgnull (NSG) mice engrafted with human HNSCC.Results High B7-H3 expression was found in HPV− HNSCC cell lines, even when the FA gene was knocked out, and The Cancer Genome Atlas patient data showed that high B7-H3 expression predicted poor survival in patients with HPV− HNSCC. Similar to the NK cell activity seen with healthy donors, the B7H3 TriKE enhanced activation, expansion and cytotoxicity of NK cells from patients with HPV− HNSCC, a target population for this therapeutic. Additionally, the B7H3 TriKE improved NK cell cytotoxicity in a three-dimensional spheroid model of HNSCC. In both acute and prolonged hypoxia (1% oxygen), the B7H3 TriKE mediated enhanced tumor killing, mitigating impairment of NK cell cytotoxicity in hypoxia. In vivo, the B7H3 TriKE-treated mice demonstrated substantial antitumor activity and prolonged survival.Conclusions The B7H3 TriKE is a novel immunotherapeutic approach that can overcome hypoxic suppression of NK cells in the HNSCC TME. These highly translational studies present an innovative therapy for patients with HNSCC and will be developed further for clinical application.